Prophetic Leadership for Cultivating Religious Moderation Rooted in Local Wisdom: Charting a Path to Tolerance and Harmony - Tarman, Tarman (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2022)
This research analyzes prophetic leadership in building religious moderation based on local wisdom at MTs Darud Da'wah wal Irsyad, Samarinda. Researchers use a qualitative case study approach, using interviews, observation, and documentation to collect data. Meanwhile, data analysis techniques are carried out through data display, data reduction, and conclusion. The research results show that prophetic leadership in building religious moderation based on local wisdom at MTs Darud Da'wah wal Irsyad, Samarinda, is carried out through prophetic leadership education and training, integration of local wisdom, adaptive curriculum, openness to change. The findings of this research provide implications regarding the importance of developing more structured and focused prophetic leadership education and training programs. Madrasas can design programs that hone leadership skills based on prophetic principles that have been proven effective in building religious moderation.